Klasifikasi Pola Menggunakan Jaringan Probabilistik - Sri Kusumadewi (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
More application often used pattern classification approach. Neural network is one ofsome methods that very powerful to solve that problem. In this paper, we will useprobabilistic net to solve classification of quality products problem. Let a company wants toclasified quality of its products. The first quality is Good, second quality is Fair, and thirdquality is Poor. This probabilistic net trained with 27 data training, and the result of thistraining used to identify another 20 data. The result of checking for data training show that100% accuracy. The result of testing for another 20 data show that 8 products in Goodquality, 7 products in Fair quality, and 5 products in Poor quality.Keywords: probabilistic net, classification.